2008
DOI: 10.1111/j.1750-3841.2008.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preservative Agents on the Respiration Rate of Minimally Processed Potato (Solanum tuberosum cv. Monalisa)

Abstract: The shelf life of minimally processed potatoes (MPP) is limited by enzyme-catalyzed browning reactions, with the increase in respiration being another factor that affects quality retention of this product. Sulfites are commonly used as effective preservative agents in minimally processing potatoes, but ascorbic acid and citric acid are considered natural sulfite substitutes and more accepted by consumers. The aim of this study was to study the effect of combinations of the preservative agents cited above (sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
2
10
0
2
Order By: Relevance
“…Similarly, among treatments, lowest respiration rate was recorded in the fruits treated with ascorbic acid treatment @150 ppm, whereas, the untreated (control) fruits have exhibited the highest respiration rate (Table 3). Our results are in line with the work of Petri et al (2008) who reported the decrease in respiration rate by the use of preservatives including ascorbic acid. A slight increase in respiration rate at higher concentration of ascorbic acid may be directly correlated with the extent of disease incidence.…”
Section: Respiration Ratesupporting
confidence: 93%
“…Similarly, among treatments, lowest respiration rate was recorded in the fruits treated with ascorbic acid treatment @150 ppm, whereas, the untreated (control) fruits have exhibited the highest respiration rate (Table 3). Our results are in line with the work of Petri et al (2008) who reported the decrease in respiration rate by the use of preservatives including ascorbic acid. A slight increase in respiration rate at higher concentration of ascorbic acid may be directly correlated with the extent of disease incidence.…”
Section: Respiration Ratesupporting
confidence: 93%
“…2), consistent with data of Petri et al (2008). The AA + CIA treatment, however, resulted in respiration rates consistently higher than those of untreated slices (Fig.…”
Section: Chemical Treatments and Respiration Ratessupporting
confidence: 93%
“…Based on the results of gas‐composition change, the sample dipped in AA + CM might be assumed to have the lowest respiration rate of the samples tested. It has been reported that because of the antioxidant capacity of AA and chamomile extract, they could lower respiration rate by affecting enzymes of the oxidative phosphorylation pathway (Petri and others ; Wessels and others ).…”
Section: Resultsmentioning
confidence: 99%